Analysis of mutations in 7 candidate genes for dextro- Transposition of the great arteries in Chinese population - Lei, Liming; Lin, Haoming; Zhong, Shilong; Zhang, Zhiwei; Chen, Jimei; Li, Xin-Xin; Yu, Xiyong; Liu, Xaioqing; Zhuang, Jian (Journal of Thoracic Disease; Vol 6, No 5 (May 08, 2014): Journal of Thoracic Disease, 2014)
Background: Transposition of great arteries (TGA) represents the most frequent cyanotic heart defect diagnosed in the neonatal period. Several genes had been identified to be associated with the pathogenesis of dextro-transposition of the great arteries (d-TGA). These genes are located in different chromosomes and their mutations can only explain few clinical cases. Besides, no genetic scan for TGA has been implemented in China. Methods: To evaluate whether aberrations in any of the 13 reported mutations in seven genes (MED13L, ZIC3, CFC1, NODAL, FOXH1, GDF1 and NKX2-5) could completely or in part be the genetic component involved in TGA in Chinese population, we screened 102 Chinese patients with d-TGA by direct sequencing for mutations within the seven genes. Results: We found none of the reported 13 mutations in those 102 Chinese d-TGA patients. Conclusions: These reported 13 mutations may not be a common cause of d-TGA in Chinese population due to racial variation and genetic heterogeneity of TGA. New approaches including the whole exome sequencing technology are required to effectively identify genetic variants in TGA patients in China.